Investigating financial statement fraud: a bibliometric analysis of research publications from the last two decades / Salwana Selamat, Nazirah Naiimi and Azrul Abdullah - Selamat, Salwana; Naiimi, Nazirah; Abdullah, Azrul (Universiti Teknologi MARA, Perlis, 2023)
Financial statement fraud is a serious issue that can lead to far-reaching consequences for businesses, investors, and the economy. To better understand this issue, this study tries to examine the progress of research publications on financial statement fraud by analyzing data obtained from the Scopus database between 2003 and 2022. Descriptive bibliometric analysis was utilized to generate a bibliometric tabulation of research publications focused on significant financial statement fraud research. The analysis involved identifying patterns in research publications to determine the publication year, top authors, citation count, types of studies, journal sources, publishers, institutions, countries, and document types. By utilizing scientific quantitative analysis and statistics, this study will provide some valuable insights that help bridge the gap using bibliometric analysis. Additionally, it could improve the understanding of financial statement fraud for future research and facilitate the creation of a research agenda for academic scholars.